Rectal perforation as a complication of cystolitholapaxy; a case report - Telma Zahirian Moghadam; Hamed Mohseni Rad (Journal of Nephropathology)
Endoscopic procedures in urology are safe although simple and impossible. We report a rare catastrophic complication of cystolitholapaxy in a patient with severe urethral stenosis. Despite laparotomy one day after cystolitholapaxy because of peritonitis and loop colostomy, the patient died. Hence, the principles of prevention and extra-care and time especially in the abnormal urethra are emphasized.